Effect of biodiesel-derived by-product on the germination of common ragweed (Ambrosia artemisiifolia L.) in pot experiments - Csontos, Péter; Pocsai, Károly (JOURNAL OF LANDSCAPE ECOLOGY, 2012)
The effect of biodiesel-derived by-product (SZO= soap-like emulsion) from rape oil was examined on the germination of common ragweed (Ambrosia artemisiifolia L.) achenes in pot experiments. Soils were treated in three different doses: 2500, 5000 and 10000 liter/ha, applied in proportion to the surface area of the pots. Control soil was moistened with the same amount of tap water. Fifty ragweed achenes were sown into each pot, then the pots were placed in a refrigerator for cold treatment (35 days, +7 °C). Following cold treatment the pots were placed in an unheated greenhouse and the germination of ragweed achenes were monitored for 40 days.Common ragweed seedlings emerged from soils of each treatment including the control, but their rate of germination differed. The highest number of seedlings appeared in the control pots (51.5%), whereas the lowest number was observed in the 2500 l/ha dose pots (33.0%). Order of the treatments according to increasing germination succes was the following: 2500 < 10000 < 5000 < control. Germination rate in treatments 2500 l/ha and 10000 l/ha was significantly lower than it was detected in the control. SZO dose of 5000 l/ha resulted intermediate germination rate of ragweed achenes, that did not differ significantly from any other treatments.Based on the results, the studied biodiesel-derived by-product can potentially be used in weed control. For its appropriate use, the effective chemical components of the SZO should be identified. Further studies needed to determine the optimal dose applicable in field management and to investigate the potential effect of SZO on the germination of cultivated species.
Keywords: biodiesel-derived by-product; common ragweed; germination; herbicide effect